1973
DOI: 10.1128/jvi.11.5.730-735.1973
|View full text |Cite
|
Sign up to set email alerts
|

Enzymatic Iodination of Sindbis Virus Proteins

Abstract: Sindbis virus was iodinated by using the enzyme lactoperoxidase, an iodination technique which labels only surface proteins. By this technique, the two viral glycoproteins are labeled, and the internal viral protein is not. The two glycoproteins are iodinated to strikingly different extents. This difference in susceptibility to iodination apparently is due to the position or conformation of the glycoproteins in the envelope spikes of the virion and not to differing contents of tyrosine, the amino acid substrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
56
0

Year Published

1974
1974
2009
2009

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 98 publications
(61 citation statements)
references
References 21 publications
5
56
0
Order By: Relevance
“…Phinney et al [55] also found that E2 protected E1 from trypsinisation and iodination at neutral pH although E1 became highly trypsin sensitive after exposure of the virus to acid pH. This is in agreement with earlier studies since iodination was known to detect more tyrosine on E2 than on E1 [72]. Biotinylation studies of exposed lysines on the surface of infectious Sindbis virus identified several sites on E2 (K70, 76,97,131,149,202,235) confirming the location of aa 202 in the exposed distal tip cluster [73].…”
Section: Figure 2 (A) a Non-reducing Page Of E1 And E2 Extracted Fromsupporting
confidence: 75%
“…Phinney et al [55] also found that E2 protected E1 from trypsinisation and iodination at neutral pH although E1 became highly trypsin sensitive after exposure of the virus to acid pH. This is in agreement with earlier studies since iodination was known to detect more tyrosine on E2 than on E1 [72]. Biotinylation studies of exposed lysines on the surface of infectious Sindbis virus identified several sites on E2 (K70, 76,97,131,149,202,235) confirming the location of aa 202 in the exposed distal tip cluster [73].…”
Section: Figure 2 (A) a Non-reducing Page Of E1 And E2 Extracted Fromsupporting
confidence: 75%
“…The lactoperoxidase catalyzed iodination reaction (Hubbard and Cohn, 1972;Sefton et al, 1973) was carried out directly in the culture medium to preserve the natural conditions and to avoid any alteration induced by washing procedures.…”
Section: Surjkce Ioditiation Oj' Cellsmentioning
confidence: 99%
“…0.2 ml packed cells was resuspended in 1.8 ml buffer A. Iodination with 50 taCi [l*q]NaI was performed as detailed by Sefton et al (29) for Sindbis virus-infected cells, except that iodination was performed in buffer A. The cells were recovered by centrifugation, and washed four times by centrifugation in buffer A.…”
Section: Iodination Of Cellsmentioning
confidence: 99%